2008
DOI: 10.1097/jcp.0b013e318185e75f
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Quetiapine Monotherapy in Rapid-Cycling Bipolar Disorder in Comparison With Sodium Valproate

Abstract: In this study, quetiapine was more effective than VPA on the number of depressive days and similar to VPA in the treatment of manic symptoms. Quetiapine was associated with a greater incidence of side effects, particularly orthostatic dysregulation, sedation, and weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Weight-gaining effect of lithium and valproate appear similar to olanzapine and quetiapine but some recent studies 61,62 suggest that it may be lower than these 2 SGAPs and comparable to that of risperidone. Patients taking olanzapine or quetiapine for maintenance of bipolar disorder may be candidates to be switched to either lithium or valproate.…”
Section: Weight Effect Of Mstsmentioning
confidence: 94%
“…Weight-gaining effect of lithium and valproate appear similar to olanzapine and quetiapine but some recent studies 61,62 suggest that it may be lower than these 2 SGAPs and comparable to that of risperidone. Patients taking olanzapine or quetiapine for maintenance of bipolar disorder may be candidates to be switched to either lithium or valproate.…”
Section: Weight Effect Of Mstsmentioning
confidence: 94%
“…Valproate was significantly better tolerated in terms of lower rates of tremor and polyuria/polydipsia although the discontinuation rate for adverse events did not differ between the two groups. The second RCT compared valproate and quetiapine monotherapy over 12 months [47]. Patients experienced less depressive days with quetiapine than valproate but the two treatments did not differ in the number of days with manic or hypomanic symptoms.…”
Section: Valproate Monotherapy In Maintenance Treatmentmentioning
confidence: 99%
“…Two RCTs have assessed valproate in the maintenance treatment of rapid cycling patients [46,47]. In one RCT, patients who had responded to combined treatment with lithium and valproate were randomized to a 20-month maintenance phase of lithium or valproate monotherapy [46].…”
Section: Valproate Monotherapy In Maintenance Treatmentmentioning
confidence: 99%
“…An RCT suggested that quetiapine was effective for rapid cyclers compared to valproic acid. 78 In post-hoc analyses of clinical studies on quetiapine in mainte-nance therapy, the quetiapine group of rapid cycling patients with bipolar I disorder showed a significantly longer period to recurrence than the placebo group. 39 Because tricyclic antidepressants are known to induce rapid cycling, it is necessary to discontinue these drugs.…”
Section: Rapid Cyclersmentioning
confidence: 99%